2014
DOI: 10.1088/1752-7155/8/2/027106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microorganisms based on headspace analysis of volatile organic compounds by gas chromatography–mass spectrometry

Abstract: The identification of specific volatile organic compounds (VOCs) produced by microorganisms may assist in developing a fast and accurate methodology for the determination of pulmonary bacterial infections in exhaled air. As a first step, pulmonary bacteria were cultured and their headspace analyzed for the total amount of excreted VOCs to select those compounds which are exclusively associated with specific microorganisms. Development of a rapid, noninvasive methodology for identification of bacterial species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 63 publications
(100 reference statements)
9
118
5
1
Order By: Relevance
“…Another important point is that the percentage of the total area that the average peaks for 2,3-Pentandione, cis-Dihydro-α-terpinyl acetate, 1-Decyne, 1,3-Heptadiene-3-yne, 2,5-dimethyl Pyrazine, Ethyl butanoate and Cyclohexene,4-ethenyl covered were at least 15%; thus, they are remarkable VOCs for S. aureus . Some of the VOCs produced by S. aureus in the current study have been reported in other studies 34, 37 but some of them have not 28, 33 . The origin of all produced VOCs is not exactly known.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Another important point is that the percentage of the total area that the average peaks for 2,3-Pentandione, cis-Dihydro-α-terpinyl acetate, 1-Decyne, 1,3-Heptadiene-3-yne, 2,5-dimethyl Pyrazine, Ethyl butanoate and Cyclohexene,4-ethenyl covered were at least 15%; thus, they are remarkable VOCs for S. aureus . Some of the VOCs produced by S. aureus in the current study have been reported in other studies 34, 37 but some of them have not 28, 33 . The origin of all produced VOCs is not exactly known.…”
Section: Discussionsupporting
confidence: 46%
“…As previous studies have shown, organisms are able to produce either common or specific VOCs 3335 . In the current study, GC-MS was used to detect VOCs generated by three pathogenic organisms in the human respiratory tract.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Various research disciplines, including environmental monitoring, biomedical diagnostics, entomology, fossil fuel exploration and food processing, have benefitted from GC technology [1][2][3][4][5] . Microfabrication technology has enabled important advancements in GC-related technologies.…”
Section: Introductionmentioning
confidence: 99%
“…This technique complements other rapid phenotyping methods such as MALDI-TOF MS for rapid culture characterization. It has been applied previously to more commonly encountered bacterial species (8-10) and used for their direct detection in exhaled breath samples (11). Production of DMS by marine algae is thought to act as a defense against oxidative stress (12) and induces apoptosis in malignant human showing the time-dependent trends that distinguish the two species.…”
mentioning
confidence: 99%